2022
DOI: 10.3390/molecules27238226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvothermal Temperature on Morphology and Supercapacitor Performance of Ni-MOF

Abstract: A series of Ni-MOF materials were synthesized via a simple hydrothermal method and can be employed as electrodes for supercapacitors (SCs). Different temperatures were selected to unveil the effect of temperature on the formation, structure, and electrochemical performance of Ni-MOF-x (x = 60, 80, 100, and 120). Ni-MOF-80 possessed a larger specific surface area with a cross-network structure formed on its surface. The synthesized Ni-MOF electrode delivered a specific capacity of 30.89 mA h g−1 when the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The architecture enabled better stability with 63.4% capacitance attained at a large current density of 30 A g −1 and good cyclicity after 2500 cycles at 10 A g −1 . Shen and colleagues then investigated the impact of solvothermal temperature on the morphology and electrochemical properties of Ni-MOF superstructures [38]. They suggested 80 • C-synthesized Ni-MOFs can form hexagonal superstructures with Ni-MOF nanofibers crossing (Figure 4e).…”
Section: Pure Mof Materialsmentioning
confidence: 99%
“…The architecture enabled better stability with 63.4% capacitance attained at a large current density of 30 A g −1 and good cyclicity after 2500 cycles at 10 A g −1 . Shen and colleagues then investigated the impact of solvothermal temperature on the morphology and electrochemical properties of Ni-MOF superstructures [38]. They suggested 80 • C-synthesized Ni-MOFs can form hexagonal superstructures with Ni-MOF nanofibers crossing (Figure 4e).…”
Section: Pure Mof Materialsmentioning
confidence: 99%
“…Additionally, the reaction temperature also plays an important role in solvothermal synthesis of MOFs. The production of MOFs, like other reactions, requires energy extraction at a certain temperature to overcome the energy barrier . Jiang et al prepared Co-MOF-74 at different temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MOF materials containing organic functional groups are regarded as the driving force for superior performance. Due to their considerable specific capacitance and adaptable structural features, these materials present enormous possibilities for energy storage [ 19 , 20 ]. For example, Qu et al [ 21 ] used the solvothermal approach to create a novel type of pillared Ni-MOF; the results showed that pillared Ni-MOFs possess a value capacitance with 552 F/g at 1 A/g.…”
Section: Introductionmentioning
confidence: 99%